Biodegradable Magnesium Alloys Promote Angio‐Osteogenesis to Enhance Bone Repair. Issue 15 (23rd June 2020) - Han, Hyung‐Seop; Jun, Indong; Seok, Hyun‐Kwang; Lee, Kang‐Sik; Lee, Kyungwoo; Witte, Frank; Mantovani, Diego; Kim, Yu‐Chan; Glyn‐Jones, Sion; Edwards, James R.
Abstract: Biodegradable metallic materials represent a potential step‐change technology that may revolutionize the treatment of broken bones. Implants made with biodegradable metals are significantly stronger than their polymer counterparts and fully biodegradable in vivo, removing the need for secondary surgery or long‐term complications. Here, it is shown how clinically approved Mg alloy promotes improved bone repair using an integrated state of the art fetal mouse metatarsal assay coupled with in vivo preclinical studies, second harmonic generation, secretome array analysis, perfusion bioreactor, and high‐resolution 3D confocal imaging of vasculature within skeletal tissue, to reveal a vascular‐mediated pro‐osteogenic mechanism controlling enhanced tissue regeneration. The optimized mechanical properties and corrosion rate of the Mg alloy lead to a controlled release of metallic Mg, Ca, and Zn ions at a rate that facilitates both angiogenesis and coupled osteogenesis for better bone healing, without causing adverse effects at the implantation site. The findings from this study support ongoing development and refinement of biodegradable metal systems to act as crucial portal technologies with significant potential to improve many clinical applications. Abstract : An integrated state‐of‐the‐art in vivo and in vitro approach reveals clinically approved Mg5Ca1Zn samples stimulate accelerated bone healing by releasing anabolic metallic ions into the surrounding tissues to enhance the growth of type H blood vessels, which localize at active sites of bone remodeling and actively recruit Osterix‐positive osteoprogenitors to the degrading implant site.